2021
DOI: 10.2989/10220119.2020.1845796
|View full text |Cite
|
Sign up to set email alerts
|

Community diversity, functional traits and adaptation of Stipa tenacissima L. under different grazing regimes in a North African arid montane rangeland

Abstract: Rangelands represent about one-third of terrestrial ecosystems around the world (Ellis and Ramankutty 2008). They provide many ecosystem services, such as forage resources, water infiltration and storage, erosion control, wildlife habitat, biodiversity and carbon sequestration (Vecchio et al. 2019). Tunisia, along with other countries in northern Africa, is currently facing degradation and desertification of its most fragile ecosystems, including the arid rangelands. The natural vegetal cover in these ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…Studies have also shown that continuous grazing leads to soil compactness, nutrient loss, inhibits compensatory growth of edible pasture, increases the proportion of inferior pasture, and decreases the diversity of community species, while reasonable grazing weakens the growth of dominant species in the community, provides survival opportunities for inferior species, increases community diversity, and then increases system productivity, which is not completely consistent with the our results (Zhang et al, 2022). Therefore, ecosystem function is closely linked to its biodiversity, but biodiversity does not necessarily provide the grazing services provided by ecosystems (Msadek, 2021).…”
Section: Effects Of Grazing System On Plant Community Characteristicscontrasting
confidence: 50%
“…Studies have also shown that continuous grazing leads to soil compactness, nutrient loss, inhibits compensatory growth of edible pasture, increases the proportion of inferior pasture, and decreases the diversity of community species, while reasonable grazing weakens the growth of dominant species in the community, provides survival opportunities for inferior species, increases community diversity, and then increases system productivity, which is not completely consistent with the our results (Zhang et al, 2022). Therefore, ecosystem function is closely linked to its biodiversity, but biodiversity does not necessarily provide the grazing services provided by ecosystems (Msadek, 2021).…”
Section: Effects Of Grazing System On Plant Community Characteristicscontrasting
confidence: 50%
“…According to the FAO, there are no available global figures but, in the USA (with the world's 4th largest land area), livestock is responsible for an estimated 55% of erosion and sediment [3]. Various authors are concerned about water [4] and wind [5] erosion, loss of grass community diversity [6], protection of ecosystem services [7,8], impact on infiltration patterns [9], enhancing carbon sequestration capacity [10], responses of exclosure of livestock [11], etc.…”
Section: Introductionmentioning
confidence: 99%